Strategic Tendencies and Prospects of Development of Fuel Ethanol Production in Russia - Aslan Zamirovich Midov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The high level of oil consumption and as a result pollution harmful emissions of carbon dioxide making it necessary to use ethanol as an additive in gasoline. The main products for the production of bioethanol are corn and sugar cane, but effectively produce fuel ethanol from the plant Sosnovsky hogweed. The paper includes investigations of the world’s major trends of bioethanol production. The work is also considered the strategic prospects for the development of fuel ethanol production in Russia and ways to solve existing problems related to the bioethanol industry.